Laser cladding powder for improving friction coefficient of cladding layer after multi-layer cladding
By using laser cladding powder with specific chemical components, the problems of easy cracking after multi-layer cladding, steel clamping and low friction coefficient are solved, and high wear resistance and high friction on the surface of the pipe rolling tool under high temperature and high pressure are achieved. coefficient extends service life.
Patent Information
- Application Number
- CN202310946085.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-31
AI Technical Summary
The existing cladding materials are prone to cracking and steel after multi-layer cladding, and have a low friction coefficient, which cannot effectively solve the wear problem of pipe rolling tools under high temperature and high pressure.
The weight percent content of chemical components is C: 0.10 to 0.30%, Si: 0.6 to 1.5%, Cr: 15.2 to 19.4%, Ni: 45.1 to 54.5%, Co: 8 to 13%, Mo: 8.00 to 12.00%, W: 2.40-6.00% of the laser cladding powder is formed by solid solution strengthening and oxide film to improve the hardness and friction coefficient of the cladding layer.
Under high temperature and high pressure conditions, the clad layer has high wear resistance and friction coefficient, avoiding cracking and steel clamping problems, and extending the service life of the pipe rolling tool.
Smart Images

Figure BDA0004366697750000071 
Figure BDA0004366697750000081 
Figure BDA0004366697750000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and in particular relates to a powder for laser cladding which can improve the friction coefficient of cladding layers after multi-layer cladding. Background Art
[0002] Seamless steel pipe is an economical steel product. In the production process of seamless steel pipe, especially in the production process of high alloy steel, the pipe rolling tools are very worn and often severely worn in the later period of service, which not only affects the surface quality of seamless pipe, but also reduces the service life, resulting in increased failure time and cost per ton of steel.
[0003] Laser cladding is a surface modification technology that uses a filler method of pre-setting cladding materials or adding cladding materials simultaneously during the processing process. The selected cladding materials containing different active elements are placed on the surface of the substrate. Under the irradiation and heating of the high-energy density laser beam, the cladding material and the surface of the substrate are melted together and rapidly cooled and solidified to prepare a cladding layer that is metallurgically bonded to the substrate. The cladding layer has excellent wear resistance, corrosion resistance, fatigue resistance, and oxidation resistance.
[0004] Chinese patent CN101974724A discloses "an iron-based alloy powder for laser cladding", whose weight percentage is 0.60-1.00% C, 0.35-0.70% Si, 0.30-0.60% Mn, 5.0-7.0% Cr, 2.5-4.0% Ni, 1.5-2.5% Mo, 1.0-1.5% W, 0.70-1.0% V, 0.20-0.40% Ti, 0.50-0.70% B, 0.20-0.40% Nb, 0.10-0.30% Ce, and the rest is Fe. The hardness of the iron-based laser cladding alloy coating is 62-67HRC, which has a high hardness, but the wear resistance is not considered, and the cracking problem of the cladding layer cannot be effectively solved.
[0005] Chinese patent CN102168211A discloses "a high temperature resistant cobalt-based alloy for heat-resistant pads of steel rolling heating furnaces", whose chemical composition weight percentage is: C 0.05-0.20%, Si 0.5-2.0%, Mn 0.5-1.5%, Cr 27-30%, Co 39-41%, Ni 14-18%, W 2-5%, Ce0.02-0.2%, and the rest is Fe. It has high creep strength and anti-oxidation and anti-corrosion properties at an operating temperature of 1300°C, and can effectively extend the service life of the heat-resistant pads. However, due to the high content of Co element, it cannot effectively solve the problem of cracking of the cladding layer after multi-layer cladding and during use. At the same time, due to the high Co content, the hardness increases and the surface friction coefficient is reduced, and the problem of steel sticking is easy to occur during the rolling process.
[0006] Chinese patent CN 111748726A discloses "a highly wear-resistant material for perforated rollers", whose chemical elements are as follows: C: 0.5-0.65%, Si: 0.2-0.6%, Mn: 1.5-1.8%, Cr: 0-0.4%, Mo: 0.3-0.8%, Ti: 1.2-3.0%, Ni: 0.3-0.7%, and the balance is Fe and other unavoidable impurities. The wear amount is 7.6-8.5mm. According to the calculation of rolling 20,000 rolls per roll change cycle, the wear amount of 10,000 rolls is 3.8-4.25mm, and the wear resistance is insufficient.
[0007] In the laser repair process of the high carbon alloy roll surface disclosed in Chinese patent CN102677049A, alloy powder is used to strengthen the iron-based alloy with Cr and Mo elements, and the alloy is formed into a matrix mainly composed of austenite after solidification by adding appropriate amounts of B and Si to meet its hardness requirements, and at the same time, it has good wettability and self-melting properties, which can prevent cracks from occurring during the cladding process. The roll surface hardness reaches more than 55HRC, but the hardness is too high, and it is easy to cause steel jamming failure when applied on the perforated roll surface, and it is easy to crack during multi-layer cladding. There is no emphasis on wear resistance under high temperature and pressure.
[0008] Since tube rolling tools have to work for a long time under high temperature and high pressure, the material structure and performance are required to have high temperature stability. High temperature wear is the main failure form of tube rolling tools. Existing cladding materials have problems such as cooling after multi-layer cladding and easy cracking and steel jamming during use, which ultimately makes them unable to be applied to laser cladding of large-size and large-surface tube rolling tools, that is, the cladding forming and use performance are poor. Summary of the invention
[0009] The purpose of the present invention is to provide a powder for laser cladding that improves the friction coefficient of the cladding layer after multi-layer cladding, which can avoid steel sticking during the cladding process. After the multi-layer laser cladding, the cladding layer still has good wear resistance under high temperature and high pressure conditions, ensuring that there is no cracking during cooling and production after the multi-layer cladding, reducing the number of steel sticking times, and is suitable for surface modification of pipe rolling tools, greatly reducing the wear rate of pipe rolling tools.
[0010] In order to achieve the above object, the present invention provides the following technical solutions:
[0011] A powder for laser cladding for improving the friction coefficient of a cladding layer after multi-layer cladding, wherein the chemical composition weight percentage is: C: 0.10-0.30%, Si: 0.6-1.5%, Cr: 15.2-19.4%, Ni: 45.1-54.5%, Co: 8-13%, Mo: 8.00-12.00%, W: 2.40-6.00%, Mn: 0.100-0.400%, Nb: 0.020-0.040%, the balance includes Fe, and the following conditions need to be satisfied at the same time: Co+W: 11.9-17.2%, Cr+Ni: 62.6-70.3%.
[0012] Furthermore, the balance is Fe.
[0013] Preferably, the average size of the powder for laser cladding is 75 to 150 um.
[0014] Furthermore, the hardness of the cladding layer obtained after laser cladding is between 215 and 239 HB.
[0015] Furthermore, the friction coefficient of the cladding layer obtained after laser cladding is between 3.9 and 5.0 at 600°C and 30N load.
[0016] In the composition design of the laser cladding powder of the present invention:
[0017] C: Improves hardness by solid solution strengthening and precipitation strengthening with other carbide-forming elements. If the C content is too high, the hardenability will be strong, and the material after multi-layer cladding will easily crack during cooling and use, resulting in performance degradation and economic losses. Therefore, the present invention controls the C content to 0.10-0.30%.
[0018] Si: provides self-fluxing property for the powder and has strong deoxidation and slag-forming ability. During the deposition process, it reacts with oxygen in the molten pool and oxides on the surface of the molten pool to form low-melting-point borosilicates that float on the surface of the molten pool, reducing the amount of oxygen and slag in the molten pool, improving the wettability of the substrate and the deposition layer and the molding properties of the deposition material. Therefore, the present invention controls the Si content to 1.5-3.0%.
[0019] Ni: By adding a certain amount of Ni, the ferrite matrix is stably transformed into an austenite matrix, thereby improving the high temperature strength and creep resistance. If the Ni content is too low, the austenite stability of the structure is insufficient, and the high temperature wear resistance is poor. If too much Ni is added, the matrix hardness will decrease, resulting in poor wear resistance. Therefore, the present invention controls the Ni content to 45.1-54.5%.
[0020] Cr: The present invention controls the Cr content to 15.2-19.4%, and at the same time, controls the Cr and Ni content to 62.6-70.3% by weight, so that stable chromium and nickel oxides and chromium-nickel spinel phase (NiCr 2 O 4 ), forming an oxide layer of 5 to 100um, on the one hand, the oxide film isolates the cladding layer and the high-temperature tube blank to avoid sticking to the steel; on the other hand, it can improve the stability of the cladding layer, which is beneficial to improve the oxidation resistance of the cladding layer, improve the wear resistance, and reduce the number of steel jams. However, if the Cr content is too high, it will cause a reduction in the addition of other alloy elements, which is not conducive to improving the hardness and wear resistance.
[0021] Co: Co has a high melting point. Adding Co is beneficial to improving the material's load-bearing capacity at high temperatures, thermal corrosion resistance, cold and thermal fatigue performance, and high-temperature creep resistance. However, if the Co content is too high, the material will be brittle, and cracking problems will easily occur during cooling after multi-layer laser cladding and during use, forming crack defects on the surface of the pipe. At the same time, a high Co content will also cause the surface hardness of the cladding layer to be high and the friction coefficient to be low, thereby causing the problem of steel sticking. Therefore, the present invention controls the Co content to be 8-13%.
[0022] W: It is the main element for improving high temperature strength. Its main function is to be dissolved in austenite, strengthen austenite and increase the recrystallization temperature of austenite, reduce alloy stacking fault energy, reduce creep rate, and improve red hardness in a high temperature environment in contact with the steel billet, ensuring that the cladding layer still has a high hardness during friction and wear. Therefore, the present invention controls the W content to 2.40-6.00%.
[0023] At the same time, the total content of Co+W elements is controlled at 11.9-17.2%, the volume percentage of γ' phase is increased, and the solid solution strengthening effect is improved to ensure that the cladding layer has good hardness. This can avoid the cladding layer from having too low hardness, severe deformation, plastic deformation, cracks, and cracking of the oxide film during use, and also avoid the cladding layer from having too high hardness, which will cause cracks in the cladding layer due to reduced plasticity during the cladding process.
[0024] Mo: Mo is also a main element for improving high temperature strength. Mo promotes the formation of MoC type carbides and has the function of stabilizing the Cr element oxide film. Adding an appropriate amount of Mo is conducive to the stable existence of the oxide film, which not only avoids steel sticking but also improves corrosion resistance, increases the friction coefficient of the cladding layer, and ensures the corrosion resistance, wear resistance and anti-steel sticking performance of the material. Therefore, the present invention controls the Mo content to 8.00-12.00%.
[0025] Nb: Nb can promote grain boundary oxidation, so that the oxide film penetrates into the grain boundary to form a jagged state, thereby improving the bonding strength between the oxide film and the substrate. Therefore, the present invention controls the Nb content to 0.020-0.040%.
[0026] The composition design features of the laser cladding powder of the present invention are:
[0027] First, the total content of Cr+Ni is limited to 62.6-70.3%, so that stable chromium and nickel oxides and chromium-nickel spinel phase (NiCr 2 O 4 ), an oxide film is formed on the surface of the cladding layer to improve the stability of the cladding layer, avoid isolating the perforated roller cladding layer substrate and the tube blank metal, and avoid sticking to the steel.
[0028] Second, through a large number of experiments conducted by the inventors, it was found that when the Co content is too high, the hardness of the cladding layer will be too high and the friction coefficient will be too low, which will cause the occurrence of steel sticking and cracking problems during use, affecting the normal use of the tube rolling tool. Therefore, the Co content must be limited to a certain range to avoid steel sticking and cracking problems.
[0029] Third, the total element content of Co+W is limited to 11.9-17.2%, which increases the volume percentage of the γ' phase and improves the solid solution strengthening effect to ensure that the cladding layer has good hardness, which can avoid the cladding layer having too low hardness and severe deformation during use, resulting in cracks and peeling of the oxide film, and can also avoid the cladding layer having too high hardness, resulting in cracks during the cladding process.
[0030] Fourth, the low C design can avoid cracking of the weld deposited layer.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention forms an oxide film with a thickness of 5 to 100 um on the surface of the cladding layer by controlling the content of Ni and Cr elements and the total content of the two elements. At the same time, by adding Mo and Nb elements, the stable existence of the oxide film is promoted to avoid steel sticking during the cladding process. At the same time, the stability of the cladding layer is improved, the oxidation resistance of the cladding layer and the friction coefficient of the cladding layer are improved, and cracking during use is avoided. The traditional improvement of wear resistance is to use alloy elements such as Cr and Mo to form fine carbides, which play a role of dispersion strengthening and enhance the high-temperature wear resistance of the substrate.
[0033] 2. The present invention combines low C, low Co and medium W design, and controls the total content of Co+W elements to 11.9-17.2%, so as to avoid the cladding layer being too hard and causing cracks in the cladding layer during use, reduce the occurrence of steel sticking problems, and also avoid the cladding layer being too hard and deformed severely and causing cracks to cause cracking and peeling of the oxide film during use.
[0034] 3. The powder of the present invention is used to perform laser cladding on the surface of a tube rolling tool. The obtained cladding layer still has a high friction coefficient under high temperature and high pressure conditions. The friction coefficient of the cladding layer obtained after laser cladding is 3.9-5.0 at 600°C and 30N load, and the hardness of the cladding layer is ensured to be 215-239HB, which effectively solves the problem of cracking or steel jamming during use after multi-layer cladding on the surface of the tube rolling tool, thereby increasing the service life of the tube rolling tool. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with specific embodiments.
[0036] The specific chemical compositions of the powders for laser cladding of the present invention and the comparative example are shown in Table 1.
[0037] The embodiment of the present invention and the comparative example adopt a 3kW semiconductor laser to prepare three cladding layers on a roller by laser cladding process, so as to improve the wear resistance of the entire roller during use.
[0038] The rollers obtained after laser cladding in the embodiments of the present invention and the comparative examples were used on the rolling line for 7 days before being taken off the line. The surface cladding layer of the rollers was observed during and after use to see whether there were cracks, steel sticking, and wear. The specific results are shown in Table 2.
[0039] The rollers obtained after laser cladding in the embodiments of the present invention and the comparative examples were tested for the high temperature friction coefficient of the cladding layer at 600°C and 30N load. See Table 2 for specific results.
[0040] The hardness of the cladding layer was measured according to the national standard GB / T 231 “Brinell hardness test for metal materials”. The specific results are shown in Table 2.
[0041] It can be seen from Table 2 that the wear loss of the cladding layer obtained in the embodiment of the present invention under high temperature and high pressure conditions is 2.3-2.9 mm / 10,000 pieces, the friction coefficient is 3.9-5.0, the hardness is 215-239 HB, and no cracking occurs during use, and the number of steel jams is greatly reduced.
[0042] In Comparative Example 1, the content of Co and Co+W is too little, and the content of Ni and Cr+Ni added is too much, resulting in a low content of high-melting-point alloy elements. The hardness can meet the requirements of the present invention, but the wear resistance is poor. Although it does not crack during use, it has a high number of steel jams.
[0043] In Comparative Example 2, the Co+W content is too high, the Cr+Ni content is too low, the hardness is high, cracks occur during use, and the cracks are wide, the friction coefficient is low, and steel sticking is serious.
[0044] In Comparative Example 3, the Co+W content is high, the Mn content is relatively high and the Nb content is relatively low, the strength is relatively high, micro cracks are generated during use, the friction coefficient is relatively low, and steel sticking is serious.
[0045] In Comparative Example 4, the Co+W content is too high, the Cr+Ni content is too low, the Mn content is relatively high and the Nb content is relatively low, the strength is relatively high, and cracks appear in the cladding layer after multi-layer cladding.
[0046] In Comparative Example 5, the Co+W content is too high, the Cr+Ni content is too low, the strength is relatively high, and cracks appear in the cladding layer after multi-layer cladding.
[0047] In Comparative Example 6, the Mo content is higher and the Nb content is lower, and the strength meets the requirements of the present invention, and there is no cracking during use, but the friction coefficient is lower, the wear amount is larger, and the number of steel jams is higher.
[0048]
[0049]
[0050]
Claims
1. A powder for laser cladding for improving the friction coefficient of a cladding layer after multi-layer cladding, wherein the chemical composition weight percentage is: C: 0.10-0.30%, Si: 0.6-1.5%, Cr: 15.2-19.4%, Ni: 45.1-54.5%, Co: 8-13%, Mo: 8.00-12.00%, W: 2.40-6.00%, Mn: 0.100-0.400%, Nb: 0.020-0.040%, the balance includes Fe, and the following conditions need to be met at the same time: Co+W: 11.9-17.2%, Cr+Ni: 62.6-70.3%.
2. The powder for laser cladding according to claim 1, characterized in that: The balance is Fe.
3. The powder for laser cladding according to claim 1 or 2, characterized in that: The average size of the powder for laser cladding is 75-150 um.
4. The powder for laser cladding according to claim 1, characterized in that: The hardness of the cladding layer obtained after laser cladding is between 215 and 239 HB.
5. The powder for laser cladding according to claim 1 or 4, characterized in that: The friction coefficient of the cladding layer obtained after laser cladding is between 3.9 and 5.0 at 600°C and 30N load.
Citation Information
Patent Citations
Iron-based alloy powder for high strength and toughness laser deposited coating
CN101974724A
High-temperature-resistant cobalt-based alloy for heat-resistant heel block of steel rolling heating furnace
CN102168211A
Laser restoring process for surface of high carbon alloy roller
CN102677049A
High-wear-resistance material for perforating roller, perforating roller and heat treatment method
CN111748726A
Laser cladding nickel base alloy powder for repairing damaged blower vane and repair method
CN105506616A